GENERALIZATION TECHNIQUE OF BALANCE IN MANAGEMENT ACCOUNTING SYSTEM - Elena A. Sharovatova (Advanced Engineering Research)
The relationship between the performance factors of the management accounting that permit to form the balance of dependent quantities in terms of revenues, expenditures and financial results, is considered. Format of the balance generalization of the dependent indices for the cost centres, cost drivers, and responsibility centres is offered.